Perancangan Database Sistem Informasi Akuntansi Penerimaan Kas Sumbangan Pembinaan Pendidikan (SPP) Berbasis Microsoft Access - Shelly Pursika; Riri Rumaizha; Tubagus Riko Rivanthio; Jonathan lucky Sasmitha (LPPM POLITEKNIK LP3I BANDUNG, 2026)
This study aims to design a database for the cash receipt accounting information system at SMK IT Baitul Aziz based on Microsoft Access. The research method used is qualitative descriptive method that explains the cash receipt procedure through data collection techniques. The data used is financial data from student tuition (SPP) payments. The results show that financial recording at SMK IT Baitul Aziz is still manual using Microsoft Excel, causing problems such as unsystematic recording, data loss due to human error, damaged data due to computer viruses, and limited data managers. The database design produces tables including student data, class data, fee components, payment data, payment SPP, and registration. The conclusion is that an automated cash receipt system is needed using a Microsoft Access database to facilitate recording and recapitulation of student payment data.